Modelling the nexus between finance, government revenue, institutional quality and sustainable energy supply in West Africa - Kayode David Kolawole; Biliqees Ayoola Abdulmumin; Gizem Uzuner; Oluwagbenga Abayomi Seyingbo; Lukman Adebayo-Oke Abdulrauf (Journal of Economic Structures, 2024)
Abstract The present study examined the relationship between finance, government revenue, institutional quality and sustainable energy supply in West Africa countries over annual frequency period from 2012 to 2020. To achieve the outlined nexus between study variables, the present study leverages on a battery of panel analysis for robust inferences. The econometric estimators employed are panel random effect regression, generalized method of moment technique. Furthermore, panel Granger causality test is utilized to analyze the direction of flow among the variables for the study. Empirical results revealed that financial development is a significant determinant of energy supply in West Africa countries while a negligible effect was reported for institutional quality and sustainable energy supply. Thus, the present study concludes that finance from financial sector is important in ensuring sufficient energy supply. To this end, this study therefore, recommends that incentives should be given to financial institutions that fund energy generation and transmission as financial development is seen to be significant on energy supply.